Studi Literatur: Peran Questioning Sebagai Scaffolding dalam Pembelajaran Matematika: Studi Literatur: Peran Questioning Sebagai Scaffolding dalam Pembelajaran Matematika - Suci Wulandari; Imrona Hayati (Jurnal Padegogik, 2022)
A review of several studies showed that the teacher's questioning skills are still not optimal, even though this is a skill possessed by the teacher. Therefore, the study of giving questions or questioning needs to be studied further. This study aimed to provide an explanation of questioning, scaffolding, the role of questioning as scaffolding in learning mathematics, and strategies for conducting questioning. This research method is literature study by collecting books and scientific journals related to questioning and scaffolding. The results of this literature study indicated that teachers need to have skills in questioning in carrying out their roles. As a form of scaffolding, questioning played a very important and quite decisive role for the success of learning mathematics. In carrying out questioning, several things need to be considered, such as a good atmosphere, short and clear questions, sufficient time to think, tracking questions, paying attention to the level of questions, and most importantly paying attention to feedback given. With questioning, it will have an impact on the development of the core quality of students' mathematics.